2002
DOI: 10.1007/s10096-001-0647-3
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia pneumoniae DNA in Peripheral Venous Blood Samples from Patients with Carotid Artery Stenosis

Abstract: In the study presented here, peripheral blood specimens obtained from patients with atherosclerosis were examined for the presence of Chlamydia pneumoniae to determine whether these specimens can be used for routine testing. Chlamydia pneumoniae DNA was detected in 7 of 56 patients with carotid stenosis and in three of four patients with other atherosclerotic diseases, but it was not detected in any of 50 healthy controls or in any of 59 age- and gender-matched patients suffering from other nonatherosclerotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
1

Year Published

2003
2003
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 15 publications
0
10
1
Order By: Relevance
“…Many additional patients returned for 11 visit during the study period to have a blood sample obtained, and none had detectable C. pneumoniae nucleic acid in PBMCs (data not shown). As summarized in table 4, our uniformly negative results are in contrast with the wide range of prevalence in 18 similar published controlled studies [4,[24][25][26][27][28].…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…Many additional patients returned for 11 visit during the study period to have a blood sample obtained, and none had detectable C. pneumoniae nucleic acid in PBMCs (data not shown). As summarized in table 4, our uniformly negative results are in contrast with the wide range of prevalence in 18 similar published controlled studies [4,[24][25][26][27][28].…”
Section: Discussioncontrasting
confidence: 85%
“…The definition of a positive PCR result is not provided in 8 of the 18 published controlled studies [4,24,26,28]. The other 10 studies used highly variable definitions of a positive result [4,25,27]; it appears that any single determination of positivity was considered to be a positive result in most of these studies [4,25]. Of interest, if we had accepted a positive result in only 1 of the replicate aliquots, then the prevalence of positivity among case patients and control subjects would have been 8.8% and 10.5%, respectively.…”
Section: Discussionmentioning
confidence: 96%
“…They found that testing 1, 3, or 5 replicates detected 3, 5, or 9 of 10 true C. pneumoniae DNA-positive PBMC samples. With this in mind, and being well-aware of the pitfalls of conventional PCR, it is not astonishing that others 14,15,24,25 reported PBMC positivity ratios in stroke patients up to 87% by means of nested PCR without repetitive testing at all.…”
Section: Discussionmentioning
confidence: 99%
“…89,97 C pneumoniae DNA was found in circulating leukocytes in patients with carotid stenosis but not in control subjects, and C pneumoniae DNA was more common than seropositivity. 98 It remains unclear whether C pneumoniae DNA correlates better with findings in plaques than serology. Seroepidemiological studies are limited by the high prevalence of antibodies in adults, by the failure to distinguish between subjects with prior infection and those with chronic infection, and by the discordance with findings in vessel walls.…”
Section: Continuous Inflammation In Matured Atherosclerotic Plaquesmentioning
confidence: 99%